2005
DOI: 10.1002/adfm.200400380
|View full text |Cite
|
Sign up to set email alerts
|

Oligothiophene-Functionalized Truxene: Star-Shaped Compounds for Organic Field-Effect Transistors

Abstract: Organic field‐effect transistors (OFETs) based on oligothiophene‐functionalized truxene derivatives have been fabricated for use as novel star‐shaped organic semiconductors in solution‐processible organic electronics. The electronic and optical properties of compounds 1–3, with increasing numbers of thiophene rings at each of the three branches, have been investigated using scanning electron microscopy (SEM), X‐ray diffraction measurements, and ultraviolet–visible (UV‐vis) and photoluminescence spectroscopies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(101 citation statements)
references
References 26 publications
2
99
0
Order By: Relevance
“…In spite of the high mobility, tetrathiafulvalene compounds also showed some poor OFET characteristics, such as large off-current at zero gate voltage VG, low on/off ratio and non-saturating behavior. For example, high mobility but poor stability were obtained with DB-TTF (37), dinaphtho-TTF (38), DT-TTF (39) and the linear benzene-fused bis(TTF) (40). 26 It has been found that a decrease in the electron donating properties is necessary in order to enhance the air stability of TTF derivatives.…”
Section: Thieno[32-b]thiophene Derivativesmentioning
confidence: 99%
“…In spite of the high mobility, tetrathiafulvalene compounds also showed some poor OFET characteristics, such as large off-current at zero gate voltage VG, low on/off ratio and non-saturating behavior. For example, high mobility but poor stability were obtained with DB-TTF (37), dinaphtho-TTF (38), DT-TTF (39) and the linear benzene-fused bis(TTF) (40). 26 It has been found that a decrease in the electron donating properties is necessary in order to enhance the air stability of TTF derivatives.…”
Section: Thieno[32-b]thiophene Derivativesmentioning
confidence: 99%
“…This C 3 -symmetric molecule can be considered as an extended p-system in which three carbazole units are sharing an aromatic ring. Surprisingly, while its all-carbon counterpart truxene has been extensively investigated for the construction of extended hydrocarbons, 7 electro-optical devices 8 or liquid crystals, 9 the triindole has been very little studied. 10 In this paper we investigate the electron-rich triindole platform as a novel redox active discotic core.…”
mentioning
confidence: 99%
“…We cooperated with Prof. Jian Pei at Peking University and synthesized star shaped thiophene derivatives( Fig. 3(8)) [32] , the mobility reaches 1.03×10 -3 cm 2 /V s. Recently, we further synthesized pyrene based butterfly shaped molecules and used them as organic field active layers (Fig. 3(9)), the mobility of the device is 3.7 ×10 -3 cm 2 /V s [43] .…”
Section: Ring and Star Shaped Compoundsmentioning
confidence: 99%
“…Fig3. Modified organic field effect materials (7) asymmetrically substituted phthalocyanine [38] (8)Star shaped [32] and (9)butterfly shaped [43] organic semiconducing compounds 8 …”
Section: Ring and Star Shaped Compoundsmentioning
confidence: 99%
See 1 more Smart Citation